2019
DOI: 10.3389/fimmu.2019.00151
|View full text |Cite
|
Sign up to set email alerts
|

Restoring T Cell Tolerance, Exploring the Potential of Histone Deacetylase Inhibitors for the Treatment of Juvenile Idiopathic Arthritis

Abstract: Juvenile Idiopathic Arthritis (JIA) is characterized by a loss of immune tolerance. Here, the balance between the activity of effector T (Teff) cells and regulatory T (Treg) cells is disturbed resulting in chronic inflammation in the joints. Presently, therapeutic strategies are predominantly aimed at suppressing immune activation and pro-inflammatory effector mechanisms, ignoring the opportunity to also promote tolerance by boosting the regulatory side of the immune balance. Histone deacetylases (HDACs) can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 133 publications
(164 reference statements)
1
20
0
Order By: Relevance
“…Histone deacetylases (HDACs) are acetylation ‘erasers’ that can deacetylate both histone and non-histone proteins. HDACs are involved in cellular signaling, epigenetic regulation, and important in regulating the function of Teff cells and Treg cells [ 125 ]. Besides the above mentioned HLA class II molecules related sJIA that may be suitable to use abatacept, studies showed the epigenetic effects of HDAC9 in regulating critical innate immune processes through deacetylation of histone proteins [ 126 , 127 ].…”
Section: Epigenomics Study Of Jiamentioning
confidence: 99%
“…Histone deacetylases (HDACs) are acetylation ‘erasers’ that can deacetylate both histone and non-histone proteins. HDACs are involved in cellular signaling, epigenetic regulation, and important in regulating the function of Teff cells and Treg cells [ 125 ]. Besides the above mentioned HLA class II molecules related sJIA that may be suitable to use abatacept, studies showed the epigenetic effects of HDAC9 in regulating critical innate immune processes through deacetylation of histone proteins [ 126 , 127 ].…”
Section: Epigenomics Study Of Jiamentioning
confidence: 99%
“…HDACs are enzymes that remove the acetyl group from nuclei histone proteins, in this way the DNA is less accessible to transcription factors. HDAC inhibitors (HDACi) are a recent class of therapeutic targets in autoimmune and neoplastic diseases39,40 . These enzymes are able to epigenetically modulate signi cant cellular functions, altering transcription and also modulating alternative post-translational lysine modi cations like methylation, ubiquitination, and sumoylation, by removing acetyl groups from proteins ε-amino lysines41 .…”
mentioning
confidence: 99%
“…Many pro-inflammatory cytokines are regulated at the epigenetic level, particularly via histone deacetylases 14 . This has made them attractive for potentially targeting cancer 15 , but also within the sphere of other pro-inflammatory conditions [16][17][18] . Natural products with epigenetic targeting activity therefore represent novel potential…”
Section: Discussionmentioning
confidence: 99%